Performance Characteristics Of Car Alternator Coupled Directly To Micro Gas Turbine (MGT) - Lim, Ching Hock (Universiti Sains Malaysia, 2018)
Rural area of Malaysia are facing problem getting power and heat supply. They have diesel engine but diesel have transportation problem and only supply energy not heat. Although rural area are full of biomass, it is not suitable used in diesel engine. Micro Gas Turbine (MGT) is smaller version of gas turbine which is the solution to rural area problem where it can run with any fuel type while provide both energy and heat but it is expensive. The current work is about developing a turbocharger MGT coupled to a generator which is more affordable. Selection of poor transmission will cause power loss to friction, high vibration and misalignment thus breakdown. Problem in pinpoint the possible defect in setup and extracting power from generator. The unsuitable extraction method will lead to most power used to overcome friction. A direct coupling was develop to connect an alternator to MGT for electrical power generation where the MGT was powered by a blower. The performance of the setup was evaluated by conducting vibration analysis. A suitable method for electrical output characterization was developed. There a total of three coupling developed for the setup and the one which are suitable is friction coupling. The setup was able to run up to maximum speed of about 12000rpm. For electrical output, alternator’s rotor was externally excited and magnetic flux is induced by the rotation of rotor by MGT through friction coupling. The suitable excitation power was determined experimentally. Maximum output power of the setup and its relationship to the rotational speed were determined by load characterization experiment with optimum excitation power. Vibration analysis shows that friction coupling have lower vibration amplitude compare to metal coupling from previous work. Parallel and angular misalignment become less severe as speed increased for friction coupling. The best excitation power for the alternator’s rotor is 0.81W with 18.33Ω. The maximum electrical output shows linear relationship with the rotational speed thus it is not affected by other parameter. Maximum output power with optimum power input is about 50W for current setup.